2021
DOI: 10.3389/fvets.2020.615915
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E1 Is an Efficient Molecular Tool for Forest Leech Blood Sucking

Abstract: From a survival perspective, it is hypothesized that leech saliva exhibits certain physiological effects to ensure fast blood-feeding, including analgesia, anesthesia, and anti-inflammation to stay undetected by the host and vasodilatation and anti-hemostasis to ensure a steady, rapid, and sustained blood flow to the feeding site. Many anti-hemostatic compounds have been identified in leech saliva, such as hirudin, calin, and bdellin A. However, no specific substance with direct vasodilatory and anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…In this study, the ED 50 of the I h facilitation effect by PGE1 was ~30 nM, and the concentration mainly used in this experiment was 100 nM. Consistent with previous studies, these concentration ranges are physiologically active in vivo and similar to the concentration ranges of antithrombotic action [33,34]. Moreover, the production of PGE1, which exhibits ~20 times stronger biological properties than PGE2 [4], can be determined according to the COX activity or the DGLA/AA ratio [1,35].…”
Section: The Role Of the Hcn2 Channel In Pge1-induced Mechanical Allydoniasupporting
confidence: 80%
See 1 more Smart Citation
“…In this study, the ED 50 of the I h facilitation effect by PGE1 was ~30 nM, and the concentration mainly used in this experiment was 100 nM. Consistent with previous studies, these concentration ranges are physiologically active in vivo and similar to the concentration ranges of antithrombotic action [33,34]. Moreover, the production of PGE1, which exhibits ~20 times stronger biological properties than PGE2 [4], can be determined according to the COX activity or the DGLA/AA ratio [1,35].…”
Section: The Role Of the Hcn2 Channel In Pge1-induced Mechanical Allydoniasupporting
confidence: 80%
“…A recent study reported that the EP4 receptor mediates PGE2-induced excitation via HCN2 channels by activating adenylate cyclase [14]. Other studies have suggested that the EP2 receptor subtype mediated spinal inflammatory hyperalgesia by facilitating HCN2 channels [33,34]. An EP2 blocker, AH6809, inhibited PGE1-induced facilitation of I h and PGE1-induced orofacial pain, but neither an EP1 blocker nor an EP4 blocker had the same effect.…”
Section: The Identification Of E-type Prostaglandin (Ep)-receptor Involved In Pge1-induced Painmentioning
confidence: 97%
“…It has been also reported that PGE2 could inhibit wound healing by recruiting fibroblasts to the feeding lesion 27 . In addition to PGE2, PGF2 alpha was also commonly detected in bloodsuckers with reported functions of vasodilation, platelet aggregation inhibition, anti-inflammation, and pain alleviation 25, 31 . In this study, we have detected another two PGs, i.e., PGJ2 and PGE3, in lamprey buccal gland.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins (PGs) are eicosanoid components derived from arachidonic acid through three sequential enzymatic reactions. They act as 'local hormones' and regulate a plethora of physiological processes 31,48 . PGs are a group of well-studied blood-sucking related metabolites, and they have been discovered in many bloodsuckers, including ticks [25][26][27][28] , salmon louses 29,30 and forest leeches 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation